1,25(OH)(2)Vitamin D inhibits foam cell formation and suppresses macrophage cholesterol uptake in patients with type 2 diabetes - Oh, Jisu (2009)
BACKGROUND: Cardiovascular disease is the leading cause of death among diabetics. Vitamin D deficiency is associated with increased risk of cardiovascular disease in this population. To determine the mechanism by which vitamin D deficiency mediates accelerated cardiovascular disease in patients with diabetes, we investigated the effects of active vitamin D on macrophage cholesterol deposition. METHODS AND RESULTS: We obtained macrophages from 76 obese, diabetic, hypertensive patients with vitamin D deficiency (25-hydroxyvitamin D < 80 nmol/L)(group A) and four control groups: obese, diabetic, hypertensive patients with normal vitamin D (group B, n=15), obese, non-diabetic, hypertensive patients with vitamin D deficiency (group C, n=25), and non-obese, non-diabetic, non-hypertensive patients with vitamin D deficiency (group D, n=10) or sufficiency (group E, n=10). The same patient’s macrophages from all groups were cultured in vitamin D-deficient or 1,25-dihydroxyvitamin D(3) (1,25(OH)(2)D(3)) supplemented media and exposed to modified low-density lipoprotein cholesterol. 1,25(OH)(2)D(3) suppressed foam cell formation by reducing acetylated or oxidized low-density lipoprotein cholesterol uptake in diabetics only. Conversely, deletion of the vitamin D receptor in macrophages from diabetic patients accelerated foam-cell formation induced by modified LDL. 1,25(OH)(2)D(3) downregulation of c-Jun N-terminal kinase activation reduced PPARγ expression, suppressed CD36 expression, and prevented oxLDL-derived cholesterol uptake. In addition, 1,25(OH)(2)D(3) suppression of macrophage endoplasmic reticulum stress improved insulin signaling, downregulated SR-A1expression, and prevented oxLDL and AcLDL-derived cholesterol uptake. CONCLUSION: These results identify reduced vitamin D receptor signaling as a potential mechanism underlying increased foam-cell formation and accelerated cardiovascular disease in diabetics.